2021
DOI: 10.23960/ujet.v10.i4.202103
|View full text |Cite
|
Sign up to set email alerts
|

Higher-Order Thinking Skills (HOTS) Based Reading Exercises in an EFL Textbook for the Second-Grade Students of Senior High School

Abstract: The objective of this research was to find out whether reading exercises in an EFL textbook for the second-grade students of senior high school are in accordance with HOTS indicators. This research adopted qualitative descriptive research and content analysis method. The object of this research was the reading comprehension essay questions in the Bahasa Inggris SMA/MA/SMK/MAK Kelas XI textbook published by the Ministry of Education and Culture in 2018. The items of the essay reading questions were analyzed usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 3 publications
1
13
0
Order By: Relevance
“…Therefore, the data collection and analysis technique for this study were done by the researcher itself. The researcher collect the data by using an instrument called checklist table adapted from (Pratiwi, 2014). Checklist table as the instrument will be used to answer the research question and fulfill the objective of the research.…”
Section: Checklistmentioning
confidence: 99%
“…Therefore, the data collection and analysis technique for this study were done by the researcher itself. The researcher collect the data by using an instrument called checklist table adapted from (Pratiwi, 2014). Checklist table as the instrument will be used to answer the research question and fulfill the objective of the research.…”
Section: Checklistmentioning
confidence: 99%
“…As a tool for data collection, the researchers used a checklist table proposed by Pratiwi (2014), which is based on the revised Bloom's taxonomy. Then, the researchers gathered and listed all reading comprehension questions preceded by WHquestion words from the predetermined textbook.…”
Section: Methodsmentioning
confidence: 99%
“…The learning objectives, as stated by the Ministry of National Education and Culture (2014), are to produce Indonesian citizens who are creative, critical, communicative, collaborative, and innovative through strengthening characters, skills, and cognition. Some characteristics of a textbook can be analyzed, including its layout, exercises, materials, instructions, and teaching resources (Pratiwi, 2014). One of the exercises that is essential to be investigated is the reading comprehension exercise.…”
Section: Introductionmentioning
confidence: 99%
“…It is believed that the results of this study can be useful by textbook writers and EFL teachers. Apriani (2019) aimed to obtain empirical evidence from the distribution of higher order thinking skills based on the revised edition of Bloom's taxonomy on questions in reading exercises in the Pathway to English textbook used in Bengkulu in Indonesia for 10 th grade high school students. The results showed that the distribution of Higher Order Thinking Skills in essay reading questions in the Pathway to English textbooks was low and unbalanced, because higher order thinking skills in the Pathway to English textbooks have fewer questions about reading essay practice questions, and less variation in Higher Order Thinking Skills.…”
Section: Empirical Studies On Textbook Analysismentioning
confidence: 99%